EFFECT OF DIFFERENT METHODS OF COMPONENTS SOURCE OF OUTLINE OF NEW PLANT OIL (Artemisia vulgaris L) AND AN EFFECT OF ANTIBOYTE - Hartati Sulastri; Elizabeth Betty Elok; Lilik Linawati (Jurnal Penelitian Saintek, 2014)
Mugwort (Artemisia vulgaris L) from Tawangmangu Central Java was extracted by water distillation, water steam and steam distillation. Essential oil Mugwort were analized by GCMS. The result showed that the chemical composition of mugwort essential oil from water distillation were composed of 36 compounds, water-steam distillation showed 34 compounds whereas steam distillation showed 29 compounds. Nevertheless three distillation methods gave similar 6 dominant compounds in different concentration. Six dominant compounds were 3,5-dimethyl-4-ethylidene-cyclohex-2-ene-1-one, filifolone, germacrene-D, gamma-caryophyllene, eucarvone and 1,8-cineol, the amounts of each of them was more than 3%. Bioautography test showed that mugwort essential oil have a good antibacterial effect especially to E.coli bacteria